Ductility, Toughness, and Flexural Performance of Hybrid Foamed- Normal Concrete Beams - Jaffal, Angham; Hilal, Ameer; Mahmoud, Akram (Iraqi Journal of Civil Engineering, 2024)
A study examined the ductility and toughness properties of beams made of reinforced concrete, including foamed, normal, and hybrid beams. Nine reinforced concrete beams were produced: three foamed concrete beams, three normal concrete beams, and three hybrid concrete beams. Each beam possessed identical rectangular cross-sectional dimensions of 1500 mm × 250 mm × 150 mm. The flexural parameters (ultimate load, ductility, deflection, and durability) were assessed for each type of concrete utilized. The study’s results showed that the load-bearing capacity of hybrid concrete beams was comparable to that of normal concrete beams, whereas foamed concrete beams exhibited slight improvement in their ability to carry loads. The ductility of reinforced foamed concrete beams was lesser than that of normal concrete. For over-reinforced beams, the ductility of hybrid concrete beams showed a significant improvement of 61% compared to foamed beams and an even more significant increase of 91.7% compared to normal beams. Furthermore, the hybrid concrete beam with over-reinforcement had a flexural toughness of 18.7% greater than the normal concrete beam. Suggested that a hybrid section comprising conventional and foamed concrete be utilized to decrease ductility and improve stiffness.